(untitled) (Papeles, 2024)
Introduction: Unplanned urban communities are a reality, with socioorganizational characteristics that make them vulnerable to adverse events; therefore, building a more resilient community should take place from non-formal education in disaster risk management. The intentionality of this study is to design an educational proposal where the community risk plan is used as a strategy for non-formal education in unplanned urban communities, case study: La Lagunita - Sucre, Mariche - Miranda state, Venezuela. Methodology: Qualitative - interpretative study with feasible project modality. For the collection of information, we worked with four community leaders chosen from a criteria-based sampling, to whom an interview was applied for the development of the diagnosis; the feasibility of the proposal was determined from a SWOT matrix. Results and discussion: The diagnosis allowed to recognize that the informants lack the knowledge for disaster risk management, but that they have the willingness to participate in educational interventions that train them in this particular; the SWOT matrix helped to understand that the proposal is viable. The proposal is based on a total of seven training phases, where strategies are proposed for addressing the pedagogical moments of a formal learning situation (beginning, development and closure). Conclusions: The findings underline the importance of developing training programs adapted to the specific needs of these communities, taking advantage of the strengths of community organization and the willingness for teamwork.